2016
DOI: 10.1177/1076029616680477
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thrombotic Events After Liver Transplantation

Abstract: Thromboprophylaxis is not well defined after liver transplantation (LT). The aim of this study was to evaluate the incidence of splanchnic vein thrombosis (SVT) and nonsplanchnic vein thrombosis (NSVT) after LT. Liver transplantations performed between 2009 and 2013 in our institution were reviewed. Demographic, intraoperative, and postoperative data were recorded. Low-molecular-weight heparin was only administered postoperatively if intraoperative thrombectomy was performed or in patients preoperatively antic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…We found that patients with incidental PVT had more thromboses in the liver graft early after surgery. A higher incidence of postoperative PVT in patients with previous PVT was reported by our group 28 and corroborated by others more recently 29 …”
Section: Discussionsupporting
confidence: 90%
“…We found that patients with incidental PVT had more thromboses in the liver graft early after surgery. A higher incidence of postoperative PVT in patients with previous PVT was reported by our group 28 and corroborated by others more recently 29 …”
Section: Discussionsupporting
confidence: 90%
“…The incidence of splanchnic vein thrombosis (SVT) was 2.4% with a further 2.1% diagnosed with nonsplanchnic VTE (upper/lower limb DVT or PE). 69 Of note, intraoperative thrombectomy was strongly associated with postoperative SVT as highlighted in ►Fig.…”
Section: Vena Cava/portal Vein Thrombosismentioning
confidence: 98%
“…Occurrence of splanchnic vein thrombosis (SVT) postliver transplantation (LT). Adapted from Blasi et al69 . All pretransplant SVT involved the portal vein.…”
mentioning
confidence: 99%
“…These reports showed incidences varying between 4.5 and 8.6%. [80][81][82][83][84] Notably, the study that reported an incidence of 8.6% only considered the number of deep vein thrombosis, 82 an even higher incidence would likely have been found if pulmonary embolisms had been taken into account. Importantly, none of the patients in this study received pharmacological thromboprophylaxis.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…84 In two other cohorts assessing incidence of VTE following liver transplantation, numbers on the use of prophylaxis were absent or only given when patients received anticoagulant treatment before surgery or when an intraoperative thrombectomy was performed. 80,81 Pharmacological thromboprophylaxis may also help to prevent early PVT or HAT, but to our knowledge, the effect of routine thromboprophylaxis on PVT or HAT has never been assessed in the postliver transplant population. Thromboprophylaxis has been shown to reduce the risk for PVT following partial hepatectomy, 106 suggesting a role for anticoagulation in post-transplant hepatic vessel thrombosis.…”
Section: Prevention and Treatment Of Thrombosismentioning
confidence: 99%